Penerapan Pendekatan Sains Teknologi Masyarakat Pada Materi Daur Air dalam Meningkatkan Hasil Belajar Siswa Di Kelas V SD Inpres 12/ 79 Biru 1 Kabupaten Bone - Titin Titin (Universtas Negeri Makassar, 2021)
This research uses a qualitative approach and the type of classroom action research. The problem formulation of this research is about the application and process of the Community Science Technology approach to water cycle materials that can improve the learning outcomes of fifth grade students at SD Inpres 12/79 Biru 1. on the water cycle material through the application of the Community Science Technology approach, as well as improving the process/activity of learning water cycle material through the application of the Community Science Technology approach for class V SD Inpres 12/79 Biru 1. The objects in this study are class V students at SD Inpres 12/ 79 Blue 1. Efforts are made to improve students' understanding of the water cycle concept by implementing learning at the core stage through four phases, namely the invitation phase, the exploration phase, the solution phase and the application phase. Data collection techniques used are teacher and student observations, and documentation. Based on the results of the analysis and evaluation at the reflection stage, the results showed that the application of the Community Science Technology approach was effective in improving the processes/activities and learning outcomes of the Water Cycle material in each cycle of action.